A fractional crystallization technique towards pure mega-size CsPb2Br5 single crystal films. Issue 9 (14th February 2019) - Yin, Jian; Zhang, Guodong; Tao, Xutang
Abstract : A simple method called fractional crystallization was introduced to prepare pure large-area CsPb2 Br5 single crystal films with high stability. Abstract : A facile fractional crystallization technique was developed to prepare single crystalline CsPb2 Br5 films using water as the solvent, and the films can be easily transferred onto various substrates for the device fabrication. The obtained films can be up to 600 × 600 μm 2 and decrease to 50 nm in thickness with high crystalline quality as well as temperature and air stability.